AMELIORATING POST-THAWED SEMEN OF BUFFALO BULLS USING A MILK-BASED EXTENDER SUPPLEMENTED WITH RESVERATROL - A. M. Alhelal; T. A. Abdulkareem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The objective of the current study was to investigate the influence of adding resveratrol (Res) to a milk-based extender on some post-thawed semen quality of Iraqi buffalo bulls for different preservation periods (cooling at 5˚C, 48 h, 1, and 2 months post-cryopreservation; PC). Four bulls, 3.5 to 4 years old, were used from 11th November 2020 to 1st June 2021. Semen samples were collected, pooled, and divided into four groups using different Res concentrations (0, 100, 150, and 200 μM) added to the milk extender. The Res-150 μM group exhibited higher (P≤0.01) plasma membrane, acrosome integrity percentages, and total antioxidants concentration (TAC) compared to the other groups. Sperm abnormalities and DNA damage percentages, as well as malondialdehyde (MDA) concentration, were lesser (P≤0.01) in the Res-150 μM group. Finally, Res-150 μM added to a milk-based extender increased the percentage of post-thawed live sperm and TAC in seminal plasma and minimized abnormal sperm percentage, DNA damage percentage, and MDA concentration in the seminal plasma of Iraqi buffalo bulls.